(untitled) (American Journal of Business Management, Economics and Banking, 2026)
In an era of rising public debt levels globally, the mechanisms by which nations ensure the timely servicing of their financial obligations have become a critical barometer of economic credibility. This article explores the strategic role of Debt-Service Guarantee Funds (DSGFs) as a pivotal financial mechanism for managing sovereign debt. By analyzing the operational frameworks of eight diverse economies (India, Malaysia, Turkey, Mexico, the United States, Russia, China, and Germany) this study identifies common features and distinct national adaptations. The findings indicate that dedicated guarantee funds enhance economic security by insulating debt repayment from budgetary volatility, strengthen sovereign credit ratings, and bolster investor confidence. The research concludes that while the funding sources vary (ranging from natural resource revenues to prioritized budget allocations), the underlying principle of securing debt service through dedicated mechanisms is a universal factor in maintaining financial stability and trust in international capital markets.